Review of Assessment Instruments to Measure Students’ System Thinking Skills - Johariah Johariah; Tri Jalmo; Dewi Lengkana (CV. Rayyan Dwi Bharata, 2023)
System thinking is one of the most important skills of the 21st century. System thinking helps students organize their thoughts in a meaningful way and make connections between seemingly unrelated problems. This study aims to determine the application of assessment instruments on system thinking skills based on literature review. This research uses the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate, and interpret all available research with the topic area of phenomena of interest, with certain relevant research questions totaling 11 articles. The results of the literature review study that researchers analyzed and concluded that a good and relevant assessment instrument can help evaluate system thinking skills objectively and comprehensively, the application of the assessment instrument has an impact on students, especially on the ability to think systemically and critically.